Systemic Modeling of Procedure Noncompliance and Safety Incidents in Chemical Manufacturing - Vivi Lailatul Rohmah; A.A. BGS. Dinariyana Dwi Putranta; Adithya Sudiarno (Green Publisher Indonesia, 2026)
This research analyzes the systemic causes of procedural non-compliance and safety incidents in the chemical manufacturing industry using an integrated approach combining Process Safety Management (PSM), Root Cause Analysis (RCA), the Human Factors Analysis and Classification System (HFACS), and System Dynamics. The PSM audit identified significant non-compliance within the Operating Procedures and Management of Change (MOC) elements, which were found to be the primary contributors to recurring incidents. RCA results indicate that technical and procedural deficiencies dominate the causal structure, while HFACS reveals that unsafe acts, inadequate supervision, and organizational influences substantially exacerbate procedural deviations. Qualitative findings from interviews, RCA, and HFACS were quantified through questionnaires, enabling statistical analysis of variables such as SOP compliance, training effectiveness, supervision quality, and safety culture. The System Dynamics model illustrates the causal interactions among training, supervision, risk perception, safety culture, SOP compliance, and incident frequency. Policy simulation results demonstrate that formal policy interventions are the most effective in suppressing incident escalation, technical interventions show limited standalone impact, and educational–behavioral interventions yield gradual improvements. The strongest risk reduction is achieved through multidimensional policy integration. Model validation using historical incident data shows close alignment between simulation trends and actual patterns, confirming model reliability. Thus, procedural non-compliance and safety incidents are driven by complex interactions among technical, human, and organizational factors, highlighting the need for integrated safety management strategies in high-risk industrial environments.